Update - Mixing Memory To Speed Solid-State Drives. - Boyd, J.
The pricey MacBook Air you covet, with its small, lightweight, shock-resistant solid- state drive (SSD), may have a secret. Despite their advantages, solid-state drives suffer not just from enormous price tags but also from slow performance during certain key operations. Now Korean engineers report that through a clever mix of two types of memory, they can give solid- state drives a boost without also jacking up their price. Unlike a traditional hard-disk drive, which can write new data directly over recorded data, the NAND flash memory that makes up solid-state drives requires free memory space in which to write. That's usually not a problem when you have to write large chunks of sequential data, such as a video clip. But it is a problem when you have to make frequent small additions and changes to existing data. If, for instance, you need to update a file, the original data must be copied to a fresh memory block so that the first block can be erased. The new data can then be merged with the original and written back to the first block.
Keywords: FRAM; NAND flash memory; Ferroelectric RAM; Memory block; Memory space; Sequential data; Shock-resistant solid-state drive; Slow performance